Leveraging ICT Technologies in Closing the Gender Gap - Sicat, Marie; Xu, Ankai; Mehetaj, Ermira; Ferrantino, Michael; Chemutai, Vicky (World Bank, Washington, DC, 2020)
In recent decades, the growth of information and communications technologies (ICT) and the move toward the digitalization of trade and global value chains has been radically transforming the global trade scene, with important implications for women engaged in trade. In order to identify adequate measures to reduce gender disparities, this paper reviews and discusses evidence from the existing literature, as well as presents evidence from several new empirical analyses. It also introduces two new frameworks to analyze the gender dimensions of e-commerce. Digital technologies have the potential to empower women socially and economically by creating new employment and entrepreneurial opportunities, removing trade barriers for women, enhancing access to finance and information and optimizing their business processes. For example, e-commerce substantially lowers the barriers to entry for micro-, small- and medium sized enterprises by reducing the investment needed to launch and run a business. Digital solutions that remove the need for face-to-face interactions when trading can help reduce the difficulties women business owners face, such as mobility constraints, discrimination, and in some countries even violence. As workers, digital technologies may help women overcome time and mobility constraints by connecting women to work from different locations and in flexible hours through emails, instant messaging and tele-conferences. It will also benefit women as consumers by saving time, providing access to information, reducing transaction costs, or giving them more control over the purchasing process. Yet, technology is not the silver bullet in resolving all the gender gaps in trade. This is because women’s access and use of ICTs and digital technologies tend to lag in contrast to men. The benefits of digital technologies hinges on well-designed and specifically targeted policies.